Penentuan kinetika urikase dari sel bacillus subtilis, B. megaterium, dan B. cereus - Dyah Iswantini; Novik Nurhidayat; . Trivadila; Adayani Nurjayanti (Institut Pertanian Bogor, 2011)
Uric acid concentration could be determined based on the oxidation of uric acid into alantoin in the presence of uricase. Determination of uric acid concentration is needed to diagnose the occurrence of kidney disease in gout patients. The aim of the research was to study the kinetics of uricase in Bacillus subtilis, B. megaterium, and B. cereus cells using spectrophotometry method by measurement the decrease of uric acid absorbance at 293 nm. The optimum conditions of uricase activity from the three bacterial cells occured in physiological conditions and uricase activity was stable until the second day. The values of maximum velocity (Vmax) for B. subtilis, B. megaterium, and B. cereuswere 0.1642, 0.0824, and 0.0412 mM/min, respectively. The values of Michaelis-Menten constant (Km) for B. subtilis, B. megaterium and B. cereus were 0.0003, 0.0036, and 0.0036 mM, respectively. The value of catalytic constant (kkat) for B. subtilis, B. megaterium, and B. cereus were 410.5000, 171.6667, and 257.5000 mM/min ml 00=1, respectively. Based on these results, among all bacteria tested, the highest of uricase binding with substrate in B. substilis cells was observed because of the smallest of Km value and greatest of Vmax and kkat .